Green Beauty Loyalty: Investigating the Role of Perceived Value, Product Quality, and Customer Satisfaction in Environmentally Friendly Cosmetic Products - Mawaddah, Difa Anna; Suhud, Usep; Monoarfa, Terrylina Arvinta (International Journal Of Education, Social Studies, And Management (IJESSM), 2024)
The purpose of this research is to determine the influence of perceived value, product quality on customer satisfaction and customer trust to build customer loyalty in environmentally friendly cosmetic products. This quantitative research method collects data through questionnaires. A total of 255 respondents were sampled using purposive sampling technique. The objects taken in this research were respondents who had purchased environmentally friendly cosmetic products at least 3 times in DKI Jakarta and were at least 18 years old. This research uses SPSS version 23 software and SEM (Structural Equation Model) from AMOS software to carry out the analysis and processing of research data. The results obtained in this research show that brand perceived value and product quality have a positive and significant effect on customer satisfaction and customer trust. Apart from that, customer satisfaction and customer trust have a positive and significant effect on customer loyalty.